Hubungan pola makan, umur, dan jenis kelamin dengan kejadian diabetes melitus tipe 2 di wilayah kerja Puskesmas Buntok - Frimantama, Yohanes Putra; Widodo, Tri; Widodo, Faradila; Yuliani, Ni Nyoman Sri; Lestarisa, Trilianty (Barigas: Jurnal Riset Mahasiswa, 2024)
Based on the Health Profile Report of Central Kalimantan in 2020, there were 74,405 cases of diabetes mellitus (DM). Barito Selatan Regency ranked fifth highest with 6,301 DM cases. Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia, attributed to insufficient pancreatic insulin production or ineffective insulin utilization in the body. The aim of this study is to determine the relationship between dietary patterns, age, and gender with the occurrence of type 2 diabetes mellitus (DMT2) in the Working Area of Buntok Community Health Center. This research employed an observational analytical study using a cross-sectional approach. Sampling was conducted using simple random sampling, involving 107 samples. Bivariate analysis was performed using the chi-square test. The majority of respondents were female (51.4%), with the highest age group being over 45 years old (69.2%). 50.5% exhibited poor dietary patterns, and 62.6% were non-DMT2 respondents. Bivariate analysis revealed respective p-values of 0.021, 0.010, and 0.000 for age, gender, and dietary patterns concerning DMT2 occurrence. The study concludes a significant association between age, gender, dietary patterns, and the incidence of DMT2 in the Buntok Community Health Center's Working Area.